Enhanced triacylglycerol catabolism by Carboxylesterase 1 promotes aggressive colorectal carcinoma. - Capece,D; D'Andrea,D; Begalli,F; Goracci,L; Tornatore,L; Alexander,JL; Di,Veroli A; Leow,S-C; Vaiyapuri,TS; Ellis,JK; Verzella,D; Bennett,J; et al. (Journal of Clinical Investigation, 2021)
The ability to adapt to low-nutrient microenvironments is essential for tumor-cell survival and progression in solid cancers, such as colorectal carcinoma (CRC). Signaling by the NF-κB transcription-factor pathway associates with advanced disease stages and shorter survival in CRC patients. NF-κB has been shown to drive tumor-promoting inflammation, cancer-cell survival and intestinal epithelial cell (IEC) dedifferentiation in mouse models of CRC. However, whether NF-κB affects the metabolic adaptations that fuel aggressive disease in CRC patients is unknown. Here, we identified carboxylesterase 1 (CES1) as an essential NF-κB-regulated lipase linking obesity-associated inflammation with fat metabolism and adaptation to energy stress in aggressive CRC. CES1 promoted CRC-cell survival via cell-autonomous mechanisms that fuel fatty-acid oxidation (FAO) and prevent the toxic build-up of triacylglycerols. We found that elevated CES1 expression correlated with worse outcomes in overweight CRC patients. Accordingly, NF-κB drove CES1 expression in CRC consensus molecular subtype (CMS)4, associated with obesity, stemness and inflammation. CES1 was also upregulated by gene amplifications of its transcriptional regulator, HNF4A, in CMS2 tumors, reinforcing its clinical relevance as a driver of CRC. This subtype-based distribution and unfavourable prognostic correlation distinguished CES1 from other intracellular triacylglycerol lipases and suggest CES1 could provide a route to treat aggressive CRC.